Smart Nanodrug with Nuclear Localization Sequences in the Presence of MMP‐2 To Overcome Biobarriers and Drug Resistance. Issue 8 (25th January 2019) - Mo, Liuting; Zhao, Zilong; Hu, Xiaoxiao; Yu, Xuan; Peng, Yongbo; Liu, Hui; Xiong, Mengyi; Fu, Ting; Jiang, Ying; Zhang, Xiaobing; Tan, Weihong
Abstract: A series of physiological barriers have impeded nanoparticle‐based drug formulations (NDFs) from reaching their targeted sites and achieving therapeutic outcomes. In this study, we develop size‐controllable stealth doxorubicin‐loaded nanodrug coated with CD47 peptides (DOX/sNDF‐CD47) based on supramolecular chemistry to overcome multiple biological barriers. The smart DOX/sNDF‐CD47 can efficiently decrease sequestration by macrophages and disassemble into poly(amidoamine) dendrimers with nuclear localization sequences (DOX/PAMAM‐NLS) in the presence of matrix metalloproteinase‐2 (MMP‐2). Such structure transformation endows DOX/sNDF‐CD47 with the ability of deep penetration in multicellular tumor spheroid, lysosomal escape, and nucleus localization, resulting in excellent cytotoxicity and drug resistance combating. In vivo experiments further confirmed that DOX/sNDF‐CD47 has good tumor‐targeting ability and can significantly improve therapeutic efficacy of DOX on xenograft tumor model. The ability to overcome multiple biological barriers makes sNDF‐CD47 a promising NDFs to treat cancer expressing MMP‐2 and combating drug resistance. Abstract : Smart nanodrug DOX/sNDF‐CD47, prepared via supramolecular assembly, can efficiently decrease macrophages sequestration, and disassemble into smaller nanodrug in the presence of MMP‐2. Such structural transformation makes it efficiently overcome various biological barriers and drug resistance. In vivo experiments further confirmed that DOX/sNDF‐CD47 has good tumor‐targeting ability and can significantly improve therapeutic efficacy of DOX on xenograft tumor model.